Identification of a Novel Species, Cladonema digitatum sp. nov. (Cnidaria: Hydrozoa: Cladonematidae), Using DNA Barcoding and Life Cycle Analyses - Fang, Xinyu; Lin, Shen; Zhang, Yuting; Wang, Zonghua; Zhou, Konglin; Chen, Jianming (Frontiers in Marine Science, 2022)
In this study, a new Cladonema species was identified in a laboratory aquarium in Fuzhou, China, and named Cladonema digitatum sp. nov. based on its morphological characteristics and DNA barcoding. It is distinct from other Cladonema medusae in having a manubrium with finger-like protuberances, radial canals with Y-shaped bifurcations, tentacles with 3–11 adhesive branches, and 3–7 stinging branches growing from the main branch as side branches. The validity of C. digitatum sp. nov. was supported by molecular phylogenetic analyses based on both mitochondrial cytochrome oxidase (COI) and mitochondrial 16S rDNA (16S) sequences. Similar to other Cladonema medusae, the adhesive and stinging branches of each tentacle, oral tentacle, manubrium, and gonads in C. digitatum displayed considerable phenotypic plasticity, thus making species identification based solely on morphology difficult. Although diagnostic characters such as filiform tentacles and medusa buds of hydroids and nematocysts are also useful for species identification in the genus Cladonema, related information is missing in some Cladonema species. Thus, information on the life cycle and DNA barcoding should be updated to describe new or cryptic species and to improve the taxonomy of the genus Cladonema.